MEMAKAI HARAJUKU STYLE: BRAND-BRAND LOKAL DAN STREET STYLE DI JEPANG - Chintya Anggraini (Fakultas Ilmu Budaya universitas Hasanuddin, 2018)
This paper discusses Harajuku style as one of the popular street styles around the world since 1990s. In many papers and studies this style has been seen through its appearances but not through the “things” being worn to create the style, such as the shirts or accessories. There is no study yet on the brands being used. In this paper 3 diferent categories of brands being identified: local brands, international brandsm local-yet-international brands. It will be explained the tensions between local identity and local brands on the one hand and global identity and mass marketing on the other, at the time Japan being integrated into the global fashion market. Through the analysis of their appearances as shown in the FRUiTs magaizen (which was the main magazine shwocasing the youths wearing Harajuku style in Tokyo), it can be seen that most brands being use were local brands.